COVID-19 Lung Pathogenesis in SARS-CoV-2 Autopsy Cases - Valdebenito, Silvana; Bessis, Simon; Annane, Djillali; Lorin de la Grandmaison, Geoffroy; Cramer–Bordé, Elisabeth; Prideaux, Brendan; Eugenin, Eliseo A.; Bomsel, Morgane (Frontiers in Immunology, 2021)
Severe acute respiratory syndrome coronavirus 2 is a major public health issue. COVID-19 is considered an airway/systemic disease, and demise has been associated with an uncontrolled immune response and a cytokine storm in response to the virus. However, the lethal mechanism of lung pathogenesis is poorly described and understood due to safety concerns. Using lung post-mortem tissues from uninfected and COVID-19 deadly cases, we identified several types of lung damage: the first, a hemorrhagic lung disease type characterized by minimal immune infiltration; second, an immune infiltration type characterized by minimal hemorrhagic events, and a third type that correspond to the combination of the two previous phenotypes. However, all three different phenotypes resulted in loss of alveolar wall integrity, detachment of large lung tissue pieces, fibroblast proliferation, and extensive fibrosis. Importantly, B cells strongly infiltrate the lung, suggesting a good local production of antibodies, but a limited T cell presence (CD3 and CD8) was observed, suggesting an exhausted or compromised immune cellular response. The mechanism of lung damage described needs to be considered in long-term COVID-19 consequences and the potential vaccine mechanism of protection against the devastating consequences of SARS-CoV-2.